Integrasi Audit Internal dan Manajemen Risiko dalam Pencegahan Fraud pada Perusahaan Ritel Besar di Indonesia: Systematic Literature Review - Nabila Dita Sabrina; Ajeng Tita Nawangsari (AKUNTANSI 45, 2026)
This study examines how internal audit and risk management work together to reduce fraud risks in large retail companies in Indonesia. Fraud cases in the retail sector continue to rise, indicating weaknesses in internal controls and limited coordination between oversight functions. To explore this issue, the study employs a Systematic Literature Review (SLR) based on the guidelines of Kitchenham and Charters (2007). Relevant articles were collected from Scopus, Emerald Insight, Google Scholar, and nationally accredited journals using keywords related to internal audit, risk management, and fraud prevention. From 143 studies identified, 25 met the inclusion criteria for detailed analysis. The review shows that aligning internal audit with risk management strengthens fraud monitoring by improving early detection, reinforcing preventive controls, and supporting risk-based governance. The adoption of data analytics, whistleblowing mechanisms, and strong ethical values further enhances organizational resilience against fraud. This study highlights the importance of integrated oversight functions for building effective and sustainable fraud prevention systems in the retail industry.